Eksperimen Pembelajaran Matematika Dengan Strategi Jigsaw dan Bamboo Dancing Terhadap Hasil Belajar Matematika Ditinjau Dari Motivasi Siswa Kelas X Smk Negeri 9 Surakarta Tahun 2015/2016 - Fitriana, Laela, Drs. Slamet H.W, M.Pd (2016)
The purpose of the research are to analyze: (1) the effect of learning strategies Jigsaw and Bamboo Dancing on learning outcomes. (2) the effect student motivation for learning outcomes. (3) the interaction between learning strategy Jigsaw and Bamboo Dancing terms of motivation on learning outcomes. Type of research quantitative with quasi experimental design. Samples were taken by Cluster random sampling of the population of all students of class X SMK Negeri 9 Surakarta academic year 2015/2016. Data collection techniques by using questionnaires, tests and documentation. Before to the analysis, first tested the normality and homogeneity test. The hypotesistest use unbalance two way analysis of variance with α = 5%. The results of this study showed: (1) there was the effect of learning strategies Jigsaw and Bamboo Dancing on learning outcomes. (2) there was not effect student motivation for learning outcomes. (3) there was not interaction between the learning strategies Jigsaw and Bamboo Dancing and motivation on learning outcomes.